How does school climate impact academic achievement? An examination of social identity processes. (February 2017) - Reynolds, Katherine J.; Lee, Eunro; Turner, Isobel; Bromhead, David; Subasic, Emina
In explaining academic achievement, school climate and social belonging (connectedness, identification) emerge as important variables. However, both constructs are rarely explored in one model. In the current study, a social psychological framework based on the social identity perspective (Turner, Hogg, Oakes, Reicher, & Wetherell, 1987) is introduced that provides a way to integrate these two areas of enquiry. Using this framework, the current study ( N  = 340 grade 7 and 9 students) investigates: (a) school climate and social identification as distinct predictors of academic achievement; and (b) social identification as a mediator of the school climate and achievement relationship. Achievement in reading, numeracy and writing was assessed by a national standardized test. The three variables most significantly associated with achievement were parental education, socio-economic status, and school identification. In line with predictions, school identification fully mediated the relationship between school climate and academic achievement in numeracy and writing, but not reading. The research highlights the importance of feeling psychologically connected to the school as a group for academic success.